Micro Foundations of Earnings Differences - Tirthatanmoy Das; Solomon Polachek (Institute of Labor Economics (IZA), 2017)
This paper examines how human capital based approaches explain the distribution of earnings. It assesses traditional, quasi-experimental, and new micro-based structural models, the latter of which gets at population heterogeneity by estimating individual-specific earnings function parameters. The paper finds one's ability to learn and one's ability to retain knowledge are most influential in explaining earnings variations. Marketable skills actually acquired in school depend on these two types of ability. However, schools may also implement ability enhancing interventions which can play a role in improving learning outcomes. Policy initiatives that improve these abilities would be a possible strategy to increase earnings and lower earnings disparity.
Keywords: I3; J3; J7; 330; earnings distribution; human capital; heterogeneity; ability